Long-term effect of the perindopril/indapamide/amlodipine single-pill combination on left ventricular hypertrophy in outpatient hypertensive subjects - Mazza, Alberto (Biomed Pharmacother, 2019)
BACKGROUND: Most antihypertensive drugs used in monotherapy or in combination therapy reduce the left ventricular mass index (LVMI). However, little is known about the effects on LVMI of a triple fixed-dose combination (TFC) therapy, containing in a single pill an angiotensin-converting enzyme inhibitor (ACEI), a diuretic and a calcium channel blocker (CCB). METHODS: In this prospective open-label study, 92 patients with essential hypertension were randomized to treatment with a TFC of perindopril/indapamide/amlodipine at different doses or a triple free combination therapy (FCT) including ACEI/diuretic/CCB. Office blood pressure (BP) measurement, 24 h-ambulatory BP monitoring and echocardiography were performed at baseline and during a 14-month follow-up. The BP variability (BPV) over 24 h was calculated as ± standard deviation of the daytime systolic BP. Differences between office and monitored BP and LVMI were evaluated by ANOVA for repeated measures. RESULTS: A significant BP-lowering effect was observed for both treatments. At follow-up, BPV was reduced in both the treatment groups vs. the baseline (14.0 ± 1.5 vs. 17.0 ±1.8 and 16.2 ± 2.1 vs. 17.6 ± 2.3, respectively), but it was lower in the TFC vs. the FCT group (14.0 ± 1.5 vs. 16.1 ± 2.2, P < 0.05). LVMI was lower in both the treatment groups, but the change was greater for TFC vs. FCT (−8.3 ± 4.9% vs. −2.0 ± 2.1%, P < 0.0001). Left ventricular hypertrophy (LVH) regression was greater in the TFC vs. the FCT group (43.5% vs. 30.4%, P < 0.05). CONCLUSIONS: Independently of BP values achieved, the antihypertensive TFC therapy was more effective than FCT in LVMI reduction and LVH regression, possibly related to drugs’ intrinsic properties and to BPV modulation.